Continuing Medical Education and Maintenance of Certification. Issue 6 (November 2016) - Loughlin, Kevin R.; Granatir, Tom; Jordan, Gerald H.
Abstract : Introduction: : The ABMS (American Board of Medical Specialties) mandated maintenance of certification in 2000 for its 24 member boards. The ABU (American Board of Urology) initiated the maintenance of certification process in 2007. Methods: : A literature review using Medline® and a Google® search was performed using continuing medical education and maintenance of certification as search terms to identify pertinent literature. Results: : The relevant literature was reviewed, and a distillation of the controversial issues regarding continuing medical education and maintenance of certification was composed. Conclusions: : The body of literature reviewed supports the conclusions that maintenance of certification serves as the most reliable vehicle to ensure lifelong learning and continuing medical education alone is not sufficient.